A quantitative approach for pesticide analysis in grape juice by direct interfacing of a matrix compatible SPME phase to dielectric barrier discharge ionization-mass spectrometry. Issue 4 (22nd January 2018) - Mirabelli, Mario F.; Gionfriddo, Emanuela; Pawliszyn, Janusz; Zenobi, Renato
Abstract : We evaluated the performance of a dielectric barrier discharge ionization (DBDI) source for pesticide analysis in grape juice, a fairly complex matrix due to the high content of sugars (≈20% w/w) and pigments. Abstract : We evaluated the performance of a dielectric barrier discharge ionization (DBDI) source for pesticide analysis in grape juice, a fairly complex matrix due to the high content of sugars (≈20% w/w) and pigments. A fast sample preparation method based on direct immersion solid-phase microextraction (SPME) was developed, and novel matrix compatible SPME fibers were used to reduce in-source matrix suppression effects. A high resolution LTQ Orbitrap mass spectrometer allowed for rapid quantification in full scan mode. This direct SPME-DBDI-MS approach was proven to be effective for the rapid and direct analysis of complex sample matrices, with limits of detection in the parts-per-trillion (ppt) range and inter- and intra-day precision below 30% relative standard deviation (RSD) for samples spiked at 1, 10 and 10 ng ml −1, with overall performance comparable or even superior to existing chromatographic approaches.